2006
DOI: 10.1139/g06-070
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sugarcane mosaic virus resistance in maize in an isogenic dihybrid crossing scheme and implications for breeding potyvirus-resistant maize hybrids

Abstract: The gene action of 2 sugarcane mosaic virus (SCMV) resistance loci in maize, Scmv1 and Scmv2, was evaluated for potyvirus resistance in an isogenic background. All 4 homozygous and 5 heterozygous isogenic genotypes were produced for introgressions of the resistant donor (FAP1360A) alleles at both loci into the susceptible parent (F7) genetic background using simple sequence repeat markers. For SCMV and maize dwarf mosaic virus (MDMV), virus symptoms appeared rapidly in the 3 homozygous genotypes, with suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 28 publications
3
29
0
Order By: Relevance
“…The Scmv1 region has been reported to associate with resistance to other members of the Potyviridae family, including WSMV and MDMV [44,45]. The near isogenic line F7 RR/RR , which was used as a resistant parental line in this study, was also found to be resistant to MDMV and ZeMV [28]. According to a model proposed by Kou [46], a single gene conferring BSR may function in either basal-resistance pathways, in overlapping pathways that confer race-specific resistances, or at sites of cross-talk between different defense pathways.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The Scmv1 region has been reported to associate with resistance to other members of the Potyviridae family, including WSMV and MDMV [44,45]. The near isogenic line F7 RR/RR , which was used as a resistant parental line in this study, was also found to be resistant to MDMV and ZeMV [28]. According to a model proposed by Kou [46], a single gene conferring BSR may function in either basal-resistance pathways, in overlapping pathways that confer race-specific resistances, or at sites of cross-talk between different defense pathways.…”
Section: Discussionmentioning
confidence: 95%
“…Apart from being influenced by two major genes, resistance of maize to SCMV is also affected by genetic background and various environmental factors [13,17,18]. To obtain reliable phenotypic data, we developed a F 2 mapping population from a near-isogenic pair where the resistance allele was fixed at the Scmv2 locus, and only Scmv1 was segregating [28]. Furthermore, selection of only susceptible individuals from the F 2 population for fine-mapping of the Scmv1 locus reduced the possibility of misclassification, as heterozygotes tend to be more plastic in their response to SCMV inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…Ingvardsen et al (2010) mapped Scmv2 to a 0.28-cM region covering 1.3 Mb and suggested several candidate genes in that region of chromosome 3. Multiple studies have shown that Scmv1/Mdm1 contributes to resistance at all developmental stages after infection, whereas Scmv2 has been associated with sustained resistance several weeks after exposure to the virus (Dußle et al, 2000;Xing et al, 2006). Although these two loci have repeatedly been associated with resistance, the amount of phenotypic variation explained by Scmv1/ Mdm1 and Scmv2 has varied by population studied.…”
mentioning
confidence: 99%
“…1, hypothetical protein; 2, putative uncharacterized protein; 3, glutathione synthetase; 4, auxin binding protein 1; 5, unknown. active at later stages post SCMV infection (Xia et al, 1999;Xing et al, 2006). We characterized allelic ZmABP1 promoter activity for FAP1360A and F7 using maize protoplast transient expression assays.…”
Section: Auxin Binding Protein 1 Reinforces Resistance To Sugarcane Mmentioning
confidence: 99%